Fifty years of philosophy of religion : a select bibliography, 1955-2005 - Sanders, Andy F. (Brill, 2007)
A bibliography that lists about 10,000 titles of monographs, collections and articles in the field of the philosophy of religion and philosophical theology that appeared between 1955 and 2005. It is useful for scholars, teachers and students in the philosophy of religion, philosophical theology and systematic theology.